Hidronīmi 16.–17.gadsimta Latvijas kartēs - Balode, Laimute (Baltistica, 1998)
HYDRONYMS ON LATVIAN MAPS OF THE 16th–17th CENTURIESThe article deals with the old hydronyms which most of all are names of the largest rivers and lakes of contemporary Latvia (one cannot find small hydroobjects on ancient maps). Old forms of hydronyms show the development and changing of the name (see Astijärw – Burteneck – Burtnieku ezers; stagnum Scemovis or Saemovis – Ķerkliņu ezers; Angerbeke – Renden beke – Rinda). These waternames help to determine or to affirm the origin of the name (see Aga ‖ Agas upe, Kaņieris). Ancient dokuments and maps demonstrate interesting morphological, phonetical and graphical variants of the name which are worth investigating. Usually it is considered that the names of old maps are more or less erroneous; there are many peculiarities of the orthography of that time, but nevertheless the old forms of toponyms often help to solve etymological, semantic or morphological problems, sometimes can illustrate historical–phonetical processes in language.
Keywords: latvių kalba; onomastika; hidronimai